Teacher’s Feedback In Writing Descriptive Text Made By Students - Umar Bakri; Ozi Satria (Lembaga Pendidikan Al-Gafari, 2023)
The purpose of this study is find out teacher’s strategy in giving feedback in writing descriptive text and to identify whether or not teacher’s feedbacks affect students in writing descriptive text. This research adopts qualitative research design. In collecting the data, the researcher will attempt to collect the data using a participant observation and questioner. The data analysis, the researcher uses three steps such as reduction, data display, and conclusion drawing. The result of the observation is that the teacher’s feedback in writing English made by students is Commentary, Correction, and Minimal Marking. The result of the teacher’s interview are conducted with six students coming from low, average, and high achievers. The writer found four kinds of students’ responses namely correcting, revising, consulting, and ignoring.